The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1017/s0952523800000316
|View full text |Cite
|
Sign up to set email alerts
|

Development of flash-evoked responses in the ectostriatum of the zebra finch: An evoked potential and current-source-density analysis

Abstract: The morphological development of the tectofugal pathway in the zebra finch has recently been described in a series of studies from our laboratory. No data are currently available on the development of visual responsiveness in this pathway. We therefore investigated the development of visually evoked potentials (VEPs) in the ectostriatum, the telencephalic target area of the tectofugal pathway. Contralateral VEPs could already be recorded in 20-day-old birds, whereas ipsilateral VEPs could first be recorded in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In birds the use of visual evoked potentials was carried out with invasive techniques, with the aim of determining the origin of the potential of the individual structures of the visual pathways. As experimental animals were used pigeons and zebra finch ( Parker & Deltus , 1972 ; Engelage & Bischof , 1989 , Engelage & Bischof ; 1988 ; Bredenkotter & Bischof , 1990 ; Engelage & Bischof , 1990 ; Wu, McGoogan & Cassone, 2000 , Bredenkotter & Bischof , 2003 ). Searching the veterinary literature revealed that VEP test is not yet used in raptors with clinical purposes, and that protocols and normal reference values are lacking for these species.…”
Section: Introductionmentioning
confidence: 99%
“…In birds the use of visual evoked potentials was carried out with invasive techniques, with the aim of determining the origin of the potential of the individual structures of the visual pathways. As experimental animals were used pigeons and zebra finch ( Parker & Deltus , 1972 ; Engelage & Bischof , 1989 , Engelage & Bischof ; 1988 ; Bredenkotter & Bischof , 1990 ; Engelage & Bischof , 1990 ; Wu, McGoogan & Cassone, 2000 , Bredenkotter & Bischof , 2003 ). Searching the veterinary literature revealed that VEP test is not yet used in raptors with clinical purposes, and that protocols and normal reference values are lacking for these species.…”
Section: Introductionmentioning
confidence: 99%
“…In birds the use of visual evoked potentials was carried out with invasive techniques, with the aim of determining the origin of the potential of the individual structures of the visual pathways. As experimental animals were used pigeons and zebra finch (Parker et al 1972, Engelage et al 1989, Engelage et al 1988, Bredenkotter et al 1990, Engelage et al 1990, Wu et al 2000, Bredenkotter et al 2003. Searching the veterinary literature revealed that VEP test is not yet used in raptors with clinical purposes, and that protocols and normal reference values are lacking for these species.…”
mentioning
confidence: 99%
“…In birds the use of visual evoked potentials was carried out with invasive techniques, with the aim of determining the origin of the potential of the individual structures of the visual pathways. As experimental animals were used pigeons and zebra finch (Parker et al 1972, Engelage et al 1989, Engelage et al 1988, Bredenkotter et al 1990, Engelage et al 1990, Wu et al 2000, Bredenkotter et al 2003. Searching the veterinary literature revealed that VEP test is not yet used in raptors with clinical purposes, and that protocols and normal reference values are lacking for these species.…”
Section: Introductionmentioning
confidence: 99%